(untitled) (Economic Journal of Nepal, 2018)
The paper deals with major factors affecting on people’s participation in forest protection and management activities in the Hill area of Nepal. Local people participate in forestry programmes basically for improving quality, quantity, and density of forests that ultimately help in continuously availability of the basic forest products for their livelihood and socio-economic development. The nature and level of people’s participation is highly determined by gross household income and socio-economic factors. A multiple log regression analysis used to examine the level of people’s participation as dependent variable and gross household income along with other socio-economic factors as independent variables. Correlation coefficients, coefficient of determinants, adj-coefficient of determinants, t-test, F-test and D-W test are major tools used for data analyses. The study found that as people received more forest products and other benefits from forest protection and management in short and long term, local people significantly participate in forestry programs. As women, poor people and disadvantage groups (DAGs) of the society are the prime users of forests and forest products, they have been directly involved and also gradually increasing in forestry activities in the study area.